The Interaction Among Rhizosphere Soil Nutrients, Metabolites, and Microbes Determines the Productivity of Perennial Cultivated Grassland in Qinghai‐Tibet Plateau - Xiaofang Zhang; Yuzhen Liu; Quan Cao; Zengzeng Yang; Zehang Yu; Caidi Li; Chunping Zhang; Quanmin Dong (Ecology and Evolution)
ABSTRACT The rhizosphere, as the primary site of plant–soil –microbe interactions, plays an important role in plant productivity. The influence of plant species on rhizosphere soil properties and how this influence shapes the productivity of grassland ecosystems remains poorly understood. Therefore, this study analyzed the changes in bacterial community structure and metabolites in the rhizosphere soil of perennial cultivated grassland. The aim was to elucidate the pathways and underlying mechanisms by which soil physicochemical properties, bacterial community structure, and rhizosphere metabolites influence productivity. Taking perennial monocropping grasslands established with three common grass species from the Qinghai –Tibet Plateau as the research objects, a comprehensive study was conducted using replicated field trials. Rhizosphere soil samples were collected from Elymus breviaristatus, Festuca sinensis, and Poa pratensis. The results indicated significant differences in productivity, soil physicochemical properties, bacterial diversity, and community structure among the monocropping grasslands. Among them, ANPP (589.17 g·m−2), root biomass (3601.67 g·m−2), moisture (18.15%) and Verrucomicrobiota (3.60%) of Elymus breviaristatus are higher than those of Festuca sinensis and Poa pratensis, while the relative abundance of Firmicutes (0.82%) is lower than that of Festuca sinensis and Poa pratensis. The topological characteristics of soil bacterial networks varied among the different grass species. The abundances of metabolites consisting of phenylalanine, proline, raffinose, maltotriose, uridine, and 2‐methylbenzaldehyde differed among different treatments. Pathway analysis highlighted the upregulation of ABC transporters and pyrimidine metabolism pathways in Elymus breviaristatus compared to Festuca sinensis and Poa pratensis. Moreover, Elymus breviaristatus secreted more uridine, which prevents the recruitment of pathogenic bacteria (such as Firmicutes) and promotes the recruitment of Verrucomicrobiota, thus improving grassland productivity. These findings show that the productivity of perennial monocropping grasslands around Qinghai Lake is the result of the interaction among rhizosphere soil nutrients, metabolites, and microorganisms. From the ecological point of view, Elymus breviaristatus is more conducive to the improvement of forage yield and the restoration of degraded grassland.